A bibliometric study on Marburg virus research with prevention and control strategies - Islam, Md. Aminul; Adeiza, Shuaibu Suleiman; Amin, Mohammad Ruhul; Kaifa, Fatema Hasan; Lorenzo, Jose M.; Bhattacharya, Prosun; Dhama, Kuldeep (Frontiers in Tropical Diseases, 2023)
Marburg virus (MARV) is a pathogenic zoonotic RNA virus etiologic for Marburg virus disease (MVD), a severe hemorrhagic fever. This is a rare disease, with a high fatality rate, that spreads via infected blood or body fluids or indirectly via fomites (contaminated objects and substances such as clothed, beds, personal protective equipment, or medical equipments). A few vaccines to protect against MARV are undergoing clinical trials, but there is not yet an approved vaccine against this disease. Eventually, prevention and control guidelines should be adhered to rigorously to alleviate this infection. This bibliometric analysis aimed to harness narrative evaluation, emphasizing the significance of quantitative approaches and delineating the most thought-provoking concerns for researchers using VOSviewer software (Centre for Science and Technology Studies, Leiden University, the Netherlands). “Marburg Virus” OR “MARV” AND “Diseases” search criteria were used for the analysis of articles published between 1962 and 2022. Co-occurrence analysis was carried out, which characterized different thematic clusters. From this analysis, we found that 1688 published articles, and the number of publications increased across that period annually, with a growth rate of 8.78%. It is also conspicuous that the number of publications in the United States reached its acme during this period (i.e., 714 publications, accounting for 42.29% of the total), and the United States Army Medical Research Institute of Infectious Diseases published the most literature (i.e., 146 papers). Our study found that the three pre-eminent authors of Marburg virus papers were “FELDMANN, HEINZ“ of the National Institute of Allergy and Infectious Diseases, United States, “BECKER, STEPHAN” of the Philipps University of Marburg, Germany, and “GEISBERT, THOMAS W” of the University of Texas Medical Branch, United States. In this study we found that “JOURNAL OF VIROLOGY” has published the most pertinent literature, totaling 88 articles, followed by “The journal of Infectious Diseases”, which published 76 relevant papers, and “VIRUSES”, which published 52 corresponding papers. The most cited paper on the Marburg virus was published in Nature Medicine, with 522 total citations and 29 citations/year. Studies of the changing epidemiology and evolving nature of the virus and its ecological niche are required; breakthrough and implementation of the efficacious vaccine candidate(s), prophylaxis and therapeutic alternatives and supervision strategies, unveiling awareness-raising programs, and developing apposite and timely preparedness, prevention, and proactive control strategies are of utmost importance.